Natural mass-dependent variations in the isotopic composition of molybdenum - Barling, J; Arnold, G; Anbar, A (2001)
We present the first observations of natural mass-dependent fractionation of the isotopic composition of molybdenum (Mo), using multi-collector inductively coupled plasma mass spectrometry. Variations in the isotopic composition of Mo are reported as δ97/95Mo analytical precision of δ97/95Mo is < ± 0.25 ‰ (2σ) on natural samples. Our data demonstrate a clear offset of > 1‰ between sediments deposited under anoxic conditions (δ97/95Mo = + 1.02 to + 1.52‰0 relative to our in-house standard) and ferromanganese nodules (δ97/95Mo = -0.63 to -0.42 ‰). δ97/95 Mo of Pacific Ocean seawater (δ97/95 Mo = + 1.48 ‰) lies within the range of values for anoxic sediments, closest to modern Black Sea anoxic sediments. Molybdenites from continental ore deposits have intermediate δ97/95Mo ranging from -0.26 to + 0.09‰. Variations in the abundances of 92Mo, 95Mo, 96Mo, 97Mo and 98Mo are consistent with mass-dependent fractionation. A sporadic unidentified interference occurs at mass 94 and 100Mo is not measured. We hypothesize that the δ97/95Mo offset between anoxic sediments and ferromanganese nodules results from Mo isotope fractionation during inefficient scavenging of Mo from seawater by Mn oxides under oxic conditions. The similarity in δ97/95 Mo of anoxic sediments and seawater is consistent with the very efficient removal of Mo from seawater under anoxic conditions in the presence of H2S. The data can be interpreted in terms of a steady-state mass balance between the Mo flux into the oceans from the continents and the Mo flux out of the oceans into oxic and anoxic sediments. Such an interpretation is quantitatively consistent with existing estimates of the removal fluxes of Mo to anoxic and oxic sediments. These findings suggest that δ97/95Mo in seawater may co-vary with changes in the relative proportions of anoxic and oxic sedimentation in the oceans, and that this variation may be recorded in δ97/95Mo of anoxic sediments. Hence, the Mo isotope system may be useful in paleoredox investigations. © 2001 Elsevier Science B.V. All rights reserved.